Does mining fuel bubbles?: An experimental study on cryptocurrency markets - Lambrecht, Marco; Sofianos, Andis; Xu, Yilong (AWI discussion paper series, 2021)
The massive price bubbles of decentralized cryptocurrencies, such as Bitcoin, have created a puzzle for economists. How can a non-revenue-generating asset exhibit such extreme price dynamics, forming multiple episodes of bubbles and crashes since its creation? The answer is not straightforward, since cryptocurrencies differ in several important aspects from other conventional assets. In this paper, we investigate how key features associated with the Proof-of-Work consensus mechanism affect pricing. In a controlled laboratory experiment, we observe that the formation of price bubbles can be causally attributed to mining. Moreover, bubbles are more pronounced if the mining capacity is centralized to a small group of individuals. Analysis of the order book data reveals that miners seem to play a crucial role in bubble formation. The results demonstrate that high price volatility is an inherent feature of cryptocurrencies based on a mining protocol, which seriously limits any prospects for such assets truly becoming a medium of exchange.
Keywords: Graue Literatur